2011
DOI: 10.1371/journal.pone.0021687
|View full text |Cite
|
Sign up to set email alerts
|

Automated Microinjection of Recombinant BCL-X into Mouse Zygotes Enhances Embryo Development

Abstract: Progression of fertilized mammalian oocytes through cleavage, blastocyst formation and implantation depends on successful implementation of the developmental program, which becomes established during oogenesis. The identification of ooplasmic factors, which are responsible for successful embryo development, is thus crucial in designing possible molecular therapies for infertility intervention. However, systematic evaluation of molecular targets has been hampered by the lack of techniques for efficient delivery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…Previous work in bovine embryos identified this adaptor protein as a mediator of permanent embryo arrest [46,67]. In addition, we have recently shown that injection of recBCL2L1 stimulates mitochondrial function in stressed embryos, prevents excessive generation of ROS, and also maintains low levels of phosphorylated p66Shc [52], implicating BCL2 family members as regulators of developmental competence.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Previous work in bovine embryos identified this adaptor protein as a mediator of permanent embryo arrest [46,67]. In addition, we have recently shown that injection of recBCL2L1 stimulates mitochondrial function in stressed embryos, prevents excessive generation of ROS, and also maintains low levels of phosphorylated p66Shc [52], implicating BCL2 family members as regulators of developmental competence.…”
Section: Discussionmentioning
confidence: 81%
“…We used the cellpermeable antiapoptotic BH4 domain of BCL2L1 (transactivator of transcription [TAT]-BH4) as this peptide can suppress BAX-induced cellular demise [50,51] and can prevent induction of ROS in embryos [52]. However, we found no impact of TAT-BH4 on progression of Nlrp5 tm/tm embryos (Fig.…”
Section: Transactivator Of Transcription-bh4 and Bip Insufficient To mentioning
confidence: 98%
“…Accordingly, several studies have shown an important role of BCL2-L1 in the regulation of embryonic cell death in pig [18,34,35,41], mouse [42], human [43], and cattle [44][45][46]. In contrast, some studies have shown that the levels of BCL2-L1 transcripts did not correlated with blastocyst quality [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that, when the expression of HDAC1 is inhibited, expression of BCLXL goes down and results in apoptosis [51]. Studies conducted on mouse preimplantation embryos have also demonstrated the crucial role of BCLXL in protecting the embryos to enter ZGA phase [28,29]. Even though it is yet to be established in rabbit embryos, it is safe to assume that the embryo relies on BCLXL and HDAC1 expression to achieve ZGA.…”
Section: Discussionmentioning
confidence: 99%
“…Among which the BAX/BCLXL ratio indicates survival or death of a cell [26,27]. BCLXL was required for cell survival and development through the ZGA phase in murine preimplantation embryos and the microinjection of BCLXL could rescue embryos and aid in ZGA [28,29]. It was also shown that BCLXL has anti-proliferative effects along with anti-apoptotic properties in murine cancer cell lines [30].…”
Section: Introductionmentioning
confidence: 99%